ANALYSIS OF HUMAN RESOURCE EMPOWERMENT STRATEGY BASED ON ANALYTICAL HIERARCHY PROCESS (AHP) FOR LOCAL CREATIVE ECONOMY DEVELOPMENT - Bangsawan, Laksamana; Rohmah, Aida; Susanto, Ferry (IJISCS (International Journal of Information System and Computer Science), 2025)
This study examines effective human resource (HR) empowerment strategies to improve the local creative economy. The urgency of this research is based on the fact that the creative economy, despite being a driver of economic growth, has not reached its optimal potential due to the low capacity of local HR. This research is important to identify effective HR empowerment strategies to increase the productivity, innovation, and competitiveness of creative economy actors at the local level. The results are expected to serve as a reference for the government and stakeholders in formulating HR-based policies. The purpose of this study is to analyze the inhibiting and supporting factors of HR empowerment in the local creative economy sector, formulate strategies that are appropriate to the characteristics and needs of creative economy actors, and provide policy recommendations to increase this sector's contribution to local development. The method used is a qualitative approach with literature studies, in-depth interviews, and Focus Group Discussions (FGDs). SWOT analysis will be used to evaluate strengths, weaknesses, opportunities, and challenges, while AHP (Analytic Hierarchy Process) analysis will be used to prioritize strategies based on weighted criteria. The results of this study indicate a significant relationship between HR empowerment strategies and the improvement of the local creative economy. Through the analysis, the most effective strategy was identified as a combination of increasing technology access and business mentoring. The formulated empowerment model is applicable and evidence-based, providing policy recommendations for the government and stakeholders. Thus, this research contributes to the development.